Analisis Konteks Wacana Tulis dalam Rubrik Metropolis Kriminal Surat Kabar Harian Riau Pos - Susi Purnama Sari; Asnawi, Asnawi (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
News is built by context. Without context, there is no news because it is the context of the discourse that builds it. Every reading, one of which is news reading in newspapers, is built by context. To understand the reading material that is read, you must pay attention to the context, because the context determines the meaning of the utterance so that it can interpret the situation or scope of discussion in the discourse. The problem in this research is: What is the context of written discourse in the metropolitan rubric of the Riau Pos daily newspaper?. The purpose of this study is to describe, analyze and interpret the context of written discourse in the criminal metropolis rubric of the Riau Pos daily newspaper. The theory used in this study is the theory of Fatimah Djajasudarma (2012). This research uses a descriptive method. Data collection techniques using hermeneutic techniques. The results of this study found eight elements of the context of discourse, namely elements of background (setting and scene), participants (participants), results (ends), message (message), method (key), means (instrument), norms (norms) and type (type). genres). The element of discourse context that was found the most was the context of the participants (participants), and the element of the context of the discourse that was found the least was the context of the discourse of the mandate (message).